Impact of climatic variability on durum wheat (Triticum durum L.) yields in North Western of Algeria - Baroudi, Meterfi; Zerey, Wael El; Bouiadjra, Salaheddine Bachir (International Journal of Environment, 2016)
In semi arid region of the South West of the Mediterranean basin, low rainfall, and thermal fluctuations cause water stress situations affecting at different levels, with varying intensities, the development of durum wheat yields. This work aims to study the major climatic factors that determine water environment of durum wheat in its reproductive period and assess their trend related to yields of the grain. Comparing diagrams of Bagnoul and Gaussen, established for two periods (1913-1937 and 1977-2014), highlighted an increase in the duration of the dry season due to rising temperatures, especially summer and a decrease in volume of the seasonal rainfall involving therefore water stress during the reproductive phase of cereal. The analysis of water regime in the past three decades, for the months of March, April and May, through the application of the approach of UNESCO-FAO, highlighted a very large variability in intensity of water stress during grain development period during the last years and also the tendency of the spring season months to be more drought. This reflects the complexity of the selection for yield components in this region. International Journal of Environment Vol. 5 (1) 2016,  pp: 107-120